Effect of copolymer composition of RAFT/MADIX-derived N-vinylcaprolactam/N-vinylpyrrolidone statistical copolymers on their thermoresponsive behavior and hydrogel properties1. Issue 29 (7th August 2015) - Zhao, Xuange; Coutelier, Olivier; Nguyen, Hanh Hong; Delmas, Céline; Destarac, Mathias; Marty, Jean-Daniel
<x xml:space="preserve">Abstract</x> RAFT/MADIX statistical copolymerization of N-vinyl lactams enables to tune thermoresponsiveness and rheological properties of copolymers in aqueous solutions.